Polymeris Voglis : Historein’s Conference: Claiming History. Aspects of Contemporary Historical Culture / Katerina Tzamali : Roumanie et Bulgarie depuis les années '30: Une comparaison - Historein, Historein (Historein, 2012)
no abstract